Overview of the distribution of dental x-ray equipment in dental specialty centers (Research, Society and Development, 2022)
Introduction: The Dental Specialty Centers (CEOs) are the units providing secondary dental services of the Unified Health System (SUS), among their operating prerogatives is the availability of minimal equipment such as dental x-ray devices. The National Registry of Establishments (CNES) is responsible for giving transparency to society about public health institutions in general. Objectives: To establish the distribution of dental x-ray devices present in cities with CEO against the number of equipment used in the SUS according to CNES data. Methodology: The secondary data used come from electronic databases made available by the Ministry of Health, where the number, types of CEO, the number and situation of use of public x-ray machines were sought. Results: Most cities with CEO have functioning x-ray machines, however much data was missing from the CNES system. Conclusion: Devices are present and functioning in CEOs representing a quarter of the number of public X-rays in cities. However, there should be an intensification in charging for updating the CNES, since many do not report the situation of their devices.